DANCR promotes septic cardiomyopathy by enhancing macrophage glycolytic reprogramming via the IGF2BP2/HK2 axis - Ma, Chunhui; Liu, Shaoyu; Zhao, Yu; Liu, Hong; Zhang, Xuguang (Frontiers in Cell and Developmental Biology, 2025)
BackgroundMetabolic reprogramming of macrophages shapes their phenotypic plasticity and contributes to the progression of septic cardiomyopathy. This study investigated the role of DANCR in modulating of macrophage glycolysis, thereby elucidating its mechanism for augmenting septic cardiomyopathy.MethodTHP-1-derived macrophages were stimulated with LPS and subjected to DANCR knockdown or HK2 overexpression. Inflammatory cytokine levels, M1 polarization, and glycolytic activity were evaluated. Conditioned media from treated macrophages were used to treat cardiomyocytes. Mechanistic analyses, including bioinformatics, RNA immunoprecipitation (RIP), and RNA stability assays, were performed to identify downstream targets of DANCR.ResultDANCR silencing attenuated M1 polarization and activity in macrophages, improved cardiomyocyte viability and reducing apoptosis. Mechanistically, DANCR upregulated HK2 expression by enhancing IGF2BP2-mediated mRNA stabilization. HK2 overexpression reversed the protective effects of DANCR knockdown, whereas pharmacologic inhibition of glycolysis counteracted the effects of HK2 overexpression, confirming the involvement of the DANCR/IGF2BP2/HK2 axis.ConclusionDANCR promotes septic cardiomyopathy by enhancing macrophage glycolytic reprogramming via the IGF2BP2/HK2 axis. Targeting this pathway may provide a novel therapeutic strategy.